Role of prebiotic dietary fiber in periodontal disease: A systematic review of animal studies - Tailor, Rohan; Medara, Nidhi; Chopra, Aditi; Swarnamali, Hasinthi; Eberhard, Joerg; Jayasinghe, Thilini N. (Frontiers in Nutrition, 2023)
Background Periodontitis is a chronic inflammatory condition affecting the supporting structures of a tooth in the oral cavity. The relationship between dietary fiber and periodontitis is poorly understood. The objective of this systematic review is to investigate if an intake of dietary fiber modulates periodontal disease in animal models and any concomitant effects on systemic inflammation, microbiota and their metabolites. Methods Animal studies using periodontitis models with any form of fiber intervention were included. Studies with comorbidities that were mutually inclusive with periodontitis and animals with physiological conditions were excluded. Search strategy with MeSH and free-text search terms were finalized and performed on the 22nd of September 2021.CINAHL Complete, EMBASE, MEDLINE, SciVerse Scopus® and Web of Science Core Collection databases were used to identify studies. SYRCLE’s risk of bias tool and CAMARADES were used for quality assessment. Results were synthesized utilizing Covidence© web-based platform software to remove duplicates, and the remaining studies were manually filtered. Results A total of 7,141 articles were retrieved from all databases. Out of 24 full-text articles assessed for eligibility, four studies (n = 4) were included. Four studies involved the use of β-(1,3/1,6)-glucan (n = 3) and mannan oligosaccharide (n = 1) at differing dosages for different study durations. All studies utilized a ligature-induced model of periodontitis in rats, either Wistar (n = 3) or Sprague–Dawley (n = 1). A dose-dependent relationship between the increased fiber intake and decrease in alveolar bone loss and pro-inflammatory markers was observed. Conclusion The number of included studies is limited and narrow in scope. They highlight the importance of pre-clinical trials in this field with broader dietary fiber intervention groups before proceeding to clinical trials. The use of dietary fiber as an intervention shows promise in the reduction of inflammatory conditions like periodontitis. However, further research is required to delineate the relationship between diet and its effects on microbiota and their metabolites such as short chain fatty acids in animal models of periodontitis.